2007
DOI: 10.1126/science.1146708
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric Anemone Jets as Evidence of Ubiquitous Reconnection

Abstract: The heating of the solar chromosphere and corona is a long-standing puzzle in solar physics. Hinode observations show the ubiquitous presence of chromospheric anemone jets outside sunspots in active regions. They are typically 3 to 7 arc seconds = 2000 to 5000 kilometers long and 0.2 to 0.4 arc second = 150 to 300 kilometers wide, and their velocity is 10 to 20 kilometers per second. These small jets have an inverted Y-shape, similar to the shape of x-ray anemone jets in the corona. These features imply that m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
365
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(394 citation statements)
references
References 24 publications
23
365
3
Order By: Relevance
“…If the generation mechanism is magnetic reconnection in the chromosphere (e.g. Shibata et al, 2007;Yurchyshyn, Abramenko, and Goode, 2013;Deng et al, 2015;Ni et al, 2015), it would indicate that there is no significant difference of magnetic structures in the chromospheric layers of CH and QS. In CH, it is probably small chromospheric loops that reconnect with open flux in the network.…”
Section: Resultsmentioning
confidence: 99%
“…If the generation mechanism is magnetic reconnection in the chromosphere (e.g. Shibata et al, 2007;Yurchyshyn, Abramenko, and Goode, 2013;Deng et al, 2015;Ni et al, 2015), it would indicate that there is no significant difference of magnetic structures in the chromospheric layers of CH and QS. In CH, it is probably small chromospheric loops that reconnect with open flux in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we infer that the intermittent coronal outflow might be caused by the chromospheric jet. In previous studies, chromospheric spicule-like jets were often reported near the solar limb, e.g., chromospheric anemone jets (Shibata et al 2007) and the type-II spicule with jet signature (De Pontieu et al 2007). Here, we find that chromospheric jets occur on the solar disk in the possible solar wind source region.…”
Section: Chromospheric Activities In the Source Regionmentioning
confidence: 99%
“…Here, we find that chromospheric jets occur on the solar disk in the possible solar wind source region. The driver of the chromospheric jet might be attributed to magnetic reconnection in the chromosphere (Shibata et al 2007;De Pontieu et al 2007) or a shock wave leaking from the photosphere along the inclined magnetic field lines (Hansteen et al 2006). …”
Section: Chromospheric Activities In the Source Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of magnetic reconnection for heating and dynamics of the solar corona was revisited by Shibata et al (2007), this time observationally with Ca ii H data from Hinode/SOT. So-called "anemone jets" were found both in the corona and in the chromosphere.…”
Section: Jetsmentioning
confidence: 99%